Modelagem do potencial geoturístico dos distritos do município de Ouro Preto - MG - Carolina de Souza Lima (2015)
The conservation of the environment is a matter of concern and discussed throughout the world. There are many initiatives aimed at raising awareness about the need to protect nature, though most of these actions consider only the biotic environment, forgetting the abiotic environment. Aiming to minimize this lack not considering the abiotic environment - the geological community turned his efforts to geoconservation, where one of the tools used is the geotourism. Geotourism is the disclosure of geosciences, the lifes history and earths formation, to society in general and accessible language to people of different knowledge levels. This research aims to model the potential geotouristic district of Ouro Preto - MG - through the Support System for Making Spatial Decisions, using the system software of Geographic Information, ArcGis 10.1. The natural tourist attractions compounds in the "Cultural Assets Protection Inventory", organized by the Ouro Preto City Hall, were quantified as the educational and recreational values of the features of geological interest, considering the risk of tourism degradation. Finally, an analysis of the intensity scores and the density was performed in the geographical area through the Kernel Density tool. The result of this research is a map which shows the geotouristic potenciality, which made it possible propose a geotouristic script in Ouro Preto districts, illustrated through the development of an interpretive map.